2004
DOI: 10.1074/jbc.m305884200
|View full text |Cite
|
Sign up to set email alerts
|

Structures of γ-Aminobutyric Acid (GABA) Aminotransferase, a Pyridoxal 5′-Phosphate, and [2Fe-2S] Cluster-containing Enzyme, Complexed with γ-Ethynyl-GABA and with the Antiepilepsy Drug Vigabatrin

Abstract: ␥-Aminobutyric acid aminotransferase (GABA-AT) is a pyridoxal 5-phosphate-dependent enzyme responsible for the degradation of the inhibitory neurotransmitter GABA. GABA-AT is a validated target for antiepilepsy drugs because its selective inhibition raises GABA concentrations in brain. The antiepilepsy drug, ␥-vinyl-GABA (vigabatrin) has been investigated in the past by various biochemical methods and resulted in several proposals for its mechanisms of inactivation. In this study we solved and compared the cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(140 citation statements)
references
References 63 publications
4
135
0
1
Order By: Relevance
“…Similarly, the deep cerebellar nuclei receive GABAergic projections from Purkinje cells. Recent studies revealed that GABA transaminase has an iron-sulfur cluster at the center of the GABA transaminase dimer (Storici et al, 2004). This enzyme is synthesized in postsynaptic neurons and astrocytes (reviewed in Kugler, 1993) and plays an essential role in the degradation of GABA, which is released from GABAergic synaptic terminals.…”
Section: Topography Of Nonheme Fe(iii) and Fe(ii) Distribution In Relmentioning
confidence: 99%
“…Similarly, the deep cerebellar nuclei receive GABAergic projections from Purkinje cells. Recent studies revealed that GABA transaminase has an iron-sulfur cluster at the center of the GABA transaminase dimer (Storici et al, 2004). This enzyme is synthesized in postsynaptic neurons and astrocytes (reviewed in Kugler, 1993) and plays an essential role in the degradation of GABA, which is released from GABAergic synaptic terminals.…”
Section: Topography Of Nonheme Fe(iii) and Fe(ii) Distribution In Relmentioning
confidence: 99%
“…FlexX performs flexible docking using an incremental fragment construction method to place a flexible ligand into a rigid protein structure. The receptor structure used was the X-ray crystal structure of two homodimers of pig liver GABA-AT in complex with vigabatrin (4-vinyl-GABA) (PDB code: 1OHW) (44). Water molecules were removed as they were found not to be located within the active site region.…”
Section: Computer Modelingmentioning
confidence: 99%
“…Reflections were indexed and integrated using XDS (13), and scaling and merging of the data were done with the program SCALA (14) from the CCP4 Software Suite (15). Phaser (16) was used for molecular replacement with a mixed input model generated by the FFAS03 server (17) on the basis of the structures of glutamate-1-semialdehyde 2,1-aminomutase from Thermus thermophilus strain HB8 (Protein Data Bank code 2E7U), D-phenylglycine aminotransferase from Pseudomonas stutzeri strain ST-201 (code 2CY8), and 4-aminobutyrate aminotransferase from pig (code 1OHV (18)). The resulting model was subjected to successive rounds of automatic model building with ARP/wARP (19), followed by manual model building in Coot (20).…”
Section: Methodsmentioning
confidence: 99%